The structure of MgtE in the absence of magnesium provides new insights into channel gating - Jin, Fei (PLoS Biol, 2021)
MgtE is a Mg(2+) channel conserved in organisms ranging from prokaryotes to eukaryotes, including humans, and plays an important role in Mg(2+) homeostasis. The previously determined MgtE structures in the Mg(2+)-bound, closed-state, and structure-based functional analyses of MgtE revealed that the binding of Mg(2+) ions to the MgtE cytoplasmic domain induces channel inactivation to maintain Mg(2+) homeostasis. There are no structures of the transmembrane (TM) domain for MgtE in Mg(2+)-free conditions, and the pore-opening mechanism has thus remained unclear. Here, we determined the cryo-electron microscopy (cryo-EM) structure of the MgtE-Fab complex in the absence of Mg(2+) ions. The Mg(2+)-free MgtE TM domain structure and its comparison with the Mg(2+)-bound, closed-state structure, together with functional analyses, showed the Mg(2+)-dependent pore opening of MgtE on the cytoplasmic side and revealed the kink motions of the TM2 and TM5 helices at the glycine residues, which are important for channel activity. Overall, our work provides structure-based mechanistic insights into the channel gating of MgtE.